Candomblé de São Paulo: fundamentos e tensões de uma comunidade terreiro na metrópole - Fernandes, Ana Paula da Silva (2017)
This research discusses the tensions, conflicts, negotiations and strategic changes that the Candomblé of São Paulo has lived to (re) exist in the metropolis. Therefore we studied the community Terreiro Ilé Axé Kalamu Funfun, located in the Municipality of extreme periphery in Franco da Rocha. Through of the called fundamentals of saint, so called by the Orisha people in their ritualistic experiences. We ponder the re-elaborations that the People of Santo paulistano ends up incorporating in Candomblé to experience it in the metropolis